2009
DOI: 10.1177/1524839909334623
|View full text |Cite
|
Sign up to set email alerts
|

Pedometers as Measurement Tools and Motivational Devices: New Insights for Researchers and Practitioners

Abstract: Pedometers are increasingly used in physical activity research and health promotion initiatives. This pilot study examines the efficacy of pedometers as motivational tools for increasing daily physical activity and exploring the practical issues related to pedometer use in research and intervention studies. A mixed-method design is used to collect data on the level of activity and in-depth information about participants' experiences wearing the pedometers. Participants are 10 midlife women between the ages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
(22 reference statements)
0
20
1
1
Order By: Relevance
“…Since Fair Play Game is an intervention package, it is difficult to attribute the increase in number of steps to one component of the strategy. For example, pedometers per se can be seen as motivators to increase active behaviours (Basett, 2000;Gardner & Campagna, 2011). However, the results of this study showed that although students were wearing pedometers before and after intervention, a significant increase in number of steps occurred after Fair Play Game was implemented in all three classes.…”
Section: Early Child Development and Carecontrasting
confidence: 52%
“…Since Fair Play Game is an intervention package, it is difficult to attribute the increase in number of steps to one component of the strategy. For example, pedometers per se can be seen as motivators to increase active behaviours (Basett, 2000;Gardner & Campagna, 2011). However, the results of this study showed that although students were wearing pedometers before and after intervention, a significant increase in number of steps occurred after Fair Play Game was implemented in all three classes.…”
Section: Early Child Development and Carecontrasting
confidence: 52%
“…consciousness-raising). 40 Baker and colleagues conducted a TTM pedometer study, 39 and randomly assigned 71 participants to: (1) a TTM pedometer intervention; (2) a TTM minutesof-activity goal-setting intervention; or (3) a control group. At week 4, the TTM pedometer group was the only group to significantly increase daily step counts (increased by 20 186 steps/week; P,0.001).…”
Section: Ttm Of Changementioning
confidence: 99%
“…Furthermore, specific goals to be attained in regard to frequency and duration of activity should be promoted. Another suggestion would be to use pedometers or other physical activity sensors as an incentive to increase NEAT as Gardner and Campagna show that such devices help increase motivation and aid in raising awareness to different activity patterns 12 . Also, self-report was used as a reporting method, where subjects may tend to over report, or simply forget.…”
Section: Discussionmentioning
confidence: 99%